2006
DOI: 10.1111/j.1551-2916.2006.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bovine Serum Albumin on the Low Temperature Synthesis of Barium Titanate Microparticles via a Solid State Route

Abstract: Fine particulate and phase pure barium titanate with its average particle size as small as 120 nm and its tetragonality as high as 1.0085 was obtained by adding bovine serum albumin (BSA) to the reactant mixture comprising fine particulate BaCO3 and TiO2. In the presence of BSA, BaCO3 decomposed at substantially lower temperatures as a consequence of coordination of BSA preferentially to the ligand field of Ba. Elimination of remaining free carbon by increasing oxygen partial pressure under flowing air was one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
(10 reference statements)
1
14
0
Order By: Relevance
“…In the course of preparing ferroelectric materials like barium titanate (BaTiO 3 , BT), the author's group has demonstrated the usefulness of mechanical activation [11][12][13]. Serious negative consequences of cationic contamination by prolonged and energy intensive milling by using milling media such as alumina, zirconia or corundum are well known.…”
Section: Consequences Of Milling a Mixture With Nylon Ballsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the course of preparing ferroelectric materials like barium titanate (BaTiO 3 , BT), the author's group has demonstrated the usefulness of mechanical activation [11][12][13]. Serious negative consequences of cationic contamination by prolonged and energy intensive milling by using milling media such as alumina, zirconia or corundum are well known.…”
Section: Consequences Of Milling a Mixture With Nylon Ballsmentioning
confidence: 99%
“…The average particle size of the BT obtained after calcining the mixture with 17 wt.% BSA was 180 nm. The tetragonality value was as high as 1.0085 [12]. The thermal decomposition behaviors of the reaction mixture and intact BSA are compared in Fig.…”
Section: Exploitation Of Further Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…BaCO 3 started to decompose and then Ba +2 ions diffused through the BaTiO 3 layer according to Eqs. In recent years, many researchers reported that ultra fine BaTiO 3 powders can be obtained directly, without the formation of the intermediate phase, Ba 2 TiO 4 , using a solid-state nanocrystalline BaCO 3 and TiO 2 reaction and mechanical activation [1][2][3][4][5][6][7][8][9][10][11][12][13]. Buscaglia et al [1] and Ando et al [2] considered using nano-crystalline BaCO 3 and TiO 2 as raw materials and mechanical activation can increase the homogeneity and contact points of the starting mixture, thereby promoting the reaction according to Eq.…”
Section: Second Stagementioning
confidence: 99%
“…However, a solid-state reaction occurring at higher temperatures easily leads to coarsening and agglomeration. Recently, a few researchers succeeded in preparing nano-sized BaTiO 3 powders using a solid state reaction below 1000 • C [1][2][3][4][5][6][7][8][9][10][11][12][13]. Therefore, the synthesis of nano-sized BaTiO 3 powder using a solid state reaction has becomes the research focus because of the lower cost, simpler process and higher productivity.…”
Section: Introductionmentioning
confidence: 99%